Screening for co-infections in patients with substance use disorders and severe bacterial infections. (October 2022) - Varley, Cara D.; Conte, Michael; Streifel, Amber C.; Winders, Bradie; Sikka, Monica K.
Background: Patients with substance use disorders admitted for severe bacterial infection are in a prime position to be screened for important co-infections. However, data suggest that standard screening for co-infections in this population during hospital admission can vary in frequency and type of testing. Methods: We performed a retrospective review of patients to evaluate screening for co-infections during admission, followed by a case–control analysis to determine factors associated with lack of any screening. Results: We identified 280 patients with 320 eligible admissions. Most were male and Caucasian with unstable housing. Only 67 (23.9%) patients had a primary-care provider. About 89% ( n = 250) of our cohort were screened for one or more co-infection during their first admission with one patient never screened despite subsequent admissions. Of those screened, the greatest proportion was HIV (219, 81.4% of those without history of HIV), HCV (94, 79.7% of those without a prior positive HCV antibody), syphilis (206, 73.6%), gonorrhea, and chlamydia (47, 16.8%) with new positive tests identified in 60 (21.4%) people. Screening for all five co-infections was only completed in 15 (14.0%) of the 107 patients who had screening indications. Overall, a high proportion of those screened had a new positive test, including three cases of neurosyphilis, highlighting the importance of screening and treatment initiation. One patient was prescribed HIV pre-exposure prophylaxis at discharge and only 37 (34.6%) of those eligible were referred for HCV treatment or follow-up. In multivariable case–control analysis, non-Medicaid insurance (OR 2.8, 95% CI: 1.2–6.6, p = 0.02), use of only 1 substance (OR 2.9, 95% CI: 1.3–6.5, p < 0.01), and no documented screening recommendations by the infectious disease team (OR 3.7, 95% CI: 1.5–8.8, p < 0.01), were statistically significantly associated with lack of screening for any co-infection during hospital admission. Conclusion: Our data suggest additional interventions are needed to improve inpatient screening for co-infections in this population.